2009
DOI: 10.1007/s11249-009-9522-7
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Oil Pockets Shape and Distribution on Seizure Resistance in Lubricated Sliding

Abstract: The results of experimental investigations on the effect of the oil pockets existence on seizure resistance of sliding elements are presented. Seizure tests were conducted with block-on-ring apparatus at increasing pressure. The stationary block (counter specimen) contacted the rotating steel ring (specimen). The tested assemblies were lubricated by oil L-AN 46, which was heated to 30°C before each experiment. The sliding was unidirectional. The block was a part of a bearing sleeve-hardened EN-GJS 400-15 cast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
24
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 31 publications
(40 reference statements)
3
24
0
2
Order By: Relevance
“…The bottoms with the converging shapes helped to minimize friction by generating hydrodynamic lift. Galda et al [30] obtained the same finding after testing dimples of the long drop shape with the sloped bottoms.…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…The bottoms with the converging shapes helped to minimize friction by generating hydrodynamic lift. Galda et al [30] obtained the same finding after testing dimples of the long drop shape with the sloped bottoms.…”
Section: Introductionsupporting
confidence: 53%
“…They found that chevron pattern pointing along the direction of motion could lead to film thickness growth. Wang [29] and Galda et al [30] observed that orientation of triangle-shaped oil pockets and dimples of long drop shape, respectively, had a substantial effect on tribological behaviors of sliding pairs. The lowest friction force was achieved when one side border orthogonal to the sliding direction first entered the contact zone.…”
Section: Introductionmentioning
confidence: 99%
“…They are called textured surfaces. Surface texturing is an option of surface engineering resulting in significant reductions of the frictional resistance in mixed and fluid lubrications, wear, and the inclination to seizure by creating oil pockets (dimples or cavities) on the sliding surfaces [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of oil-accumulating cavities on the interacting surfaces has a positive effect on lubrication but, on the other hand, leads to an increase in unit pressure. It was found that seizure resistance depends on the distribution of lubricant-accumulating cavities and their shape [3]. In shot peening, the impact of shot impacting a surface leads to formation of microcavities which can serve as "lubricant reservoirs."…”
Section: Introductionmentioning
confidence: 99%